Antimicrobial Potential of Cannabinoids: A Scoping Review of the Past 5 Years - Maria João Coelho; Maria Duarte Araújo; Márcia Carvalho; Inês Lopes Cardoso; Maria Conceição Manso; Cristina Pina (Microorganisms)
In the scenario of fighting bacterial resistance to antibiotics, natural products have been extensively investigated for their potential antibacterial activities. Among these, cannabinoids—bioactive compounds derived from cannabis—have garnered attention for their diverse biological activities, including anxiolytic, anti-inflammatory, analgesic, antioxidant, and neuroprotective properties. Emerging evidence suggests that cannabinoids may also possess significant antimicrobial properties, with potential applications in enhancing the efficacy of conventional antimicrobial agents. Therefore, this review examines evidence from the past five years on the antimicrobial properties of cannabinoids, focusing on underlying mechanisms such as microbial membrane disruption, immune response modulation, and interference with microbial virulence factors. In addition, their synergistic potential, when used alongside standard therapies, underscores their promise as a novel strategy to address drug resistance, although further research and clinical trials are needed to validate their therapeutic use. Overall, cannabinoids offer a promising avenue for the development of innovative treatments to combat drug-resistant infections and reduce the reliance on traditional antimicrobial agents.